Levels od natural resistance to Boophilus microplus( Acari: Ixodidae) in Carrora breed bulls. - Meléndez, Roy D (Universidad de Costa Rica, 1998)
Boophilus microplus infestation is one of the industry in tropical regions even though bovines show natural resistance to tick.